2010
DOI: 10.1371/journal.pone.0010041
|View full text |Cite|
|
Sign up to set email alerts
|

Pepper Mild Mottle Virus, a Plant Virus Associated with Specific Immune Responses, Fever, Abdominal Pains, and Pruritus in Humans

Abstract: BackgroundRecently, metagenomic studies have identified viable Pepper mild mottle virus (PMMoV), a plant virus, in the stool of healthy subjects. However, its source and role as pathogen have not been determined.Methods and Findings21 commercialized food products containing peppers, 357 stool samples from 304 adults and 208 stool samples from 137 children were tested for PMMoV using real-time PCR, sequencing, and electron microscopy. Anti-PMMoV IgM antibody testing was concurrently performed. A case-control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
151
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(171 citation statements)
references
References 35 publications
3
151
0
Order By: Relevance
“…Notably, PMMoV has been identified as the dominant virus in municipal wastewater from a WWTP in Arizona, US [29]. The ubiquity of PMMoV throughout different geographical locations suggests this virus to be a potential marker for tracing anthropogenic contamination [27,30]. While it remains unclear whether plant viruses cause disease in humans [31], PMMoV recovered from food samples and human feces were shown to infect hypersensitive Nicotiana tabcum var Xanthi NN at a dose of 10 8 copies [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, PMMoV has been identified as the dominant virus in municipal wastewater from a WWTP in Arizona, US [29]. The ubiquity of PMMoV throughout different geographical locations suggests this virus to be a potential marker for tracing anthropogenic contamination [27,30]. While it remains unclear whether plant viruses cause disease in humans [31], PMMoV recovered from food samples and human feces were shown to infect hypersensitive Nicotiana tabcum var Xanthi NN at a dose of 10 8 copies [30].…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquity of PMMoV throughout different geographical locations suggests this virus to be a potential marker for tracing anthropogenic contamination [27,30]. While it remains unclear whether plant viruses cause disease in humans [31], PMMoV recovered from food samples and human feces were shown to infect hypersensitive Nicotiana tabcum var Xanthi NN at a dose of 10 8 copies [30]. Compared to other viral species, both CGMMV and PMMoV were not removed by MBR completely (Figure S2), rather their molecular signatures were detected in high abundance in the final chlorinated post-MBR effluent.…”
Section: Discussionmentioning
confidence: 99%
“…), causing various symptoms such as mild chlorosis, stunting, fruit mottling, and malformation (2). Processed food products containing peppers are therefore known to contain PMMoV, with a concentration of up to 10 7 copies/ml (3,4). A recent metagenomic analysis showed that PMMoV was the most abundant RNA virus in 3 fecal samples from healthy adults in the United States, comprising 75.7 to 99.4% of all RNA viral sequences identified (4).…”
mentioning
confidence: 99%
“…Concerning the source of these viruses, we recently found that Tabasco products were contaminated at a very high level with the mild pepper virus. We showed that there is a statistical link between the presence of this virus at high load (in the feces, the virus is alive and cultivable) and clinical signs of fever, pruritis, and abdominal pain [14]. In this work, we showed that industrial products had a higher rate of contamination than local products due to the mutualization of microorganisms.…”
mentioning
confidence: 54%